Sosialisasi Peningkatan Mutu Pelayanan dan Keselamatan Pasien di Klinik Dr. Sunedi Palembang - Herdiani, Rini; S, Sunirah; Mayangsari, Junawalia (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Improving  the  quality  of  service  is  a  top  priority  in  all clinics.  These  efforts  are  carried  out  through  the construction  of  facilities,  infrastructure,  procurement  of  equipment  and  personnel  as  well  as  other  software,  in line with the construction of clinic in general. In addition to improving the quality of services, the quality of human  resources  also  needs  to  be  improved.  Human  resources  owned  by clinic will  also  affect quality  of  health  services,  the  limited  diversity  of  types  of  health  workers  will  result  in hospital  performance  in  achieving  hospital  service  quality  indicators.  One  of  the  obstacles  to  the  efforts  of clinic in providing satisfactory medical services at this time is the limited resources and supporting facilities, especially  medical  technology,  which  is  a  crucial  point  in  medical  treatment.  Medical  and  other  nursing personnel are also one of the main pillars for hospitals that can support the competitive advantage of clinic if the  management  system  and  human  resource  development  in  it  can  be  managed  properly,  which  includes fulfilling  standardized  competency  indicators,  developing  expertise  with  trainings.  and  nursing  care,  objective performance appraisal, fair distribution of working hours, as well as a compensation system that can provide job satisfaction  in  order  to  improve  individual  performance  which  leads  to  an  increase  in  overall clinic performance.  In this case, there  are  still many hospital managements who do not understand the importance of the  elements  of  service  quality  management  and  human  resource  management.  Therefore,  an  understanding  is needed clinic leaders about the importance of this for the process of improving the quality of service and the quality of performance will be a long-term investment owned.